La pragmática de la objetividad en el uso de las marcas personales en el discurso científico-académico principiante español: perspectiva polaca - Komorowska, Agata (Studia Romanica Posnaniensia, 2025)
This article focuses on the grammatical elements that pragmatically reinforce the objectivity of Spanish scientific-academic discourse, and more specifically, on the use or omission of personal brands. To this end, a series of final degree projects, written in the Spanish language by Polish university students, are examined with the aim of verifying the discursive competence of inexperienced authors in the use of different strategies aimed at granting objectivity to the scientific text and the possible problems. originated by pragmatic-grammatical interferences between the Polish and Spanish languages.